Poverty in the United States : Women's Voices - O'Leary, Ann; Frew, Paula M. (Springer International Publishing : Imprint: Springer, 2017)
This important text explores the deep relationships between poverty, health/mental health conditions, and widespread social problems as they affect the lives of low-income women. A robust source of both empirical findings and first-person descriptions by poor women of their living conditions, it exposes cyclical patterns of structural and environmental stressors contributing to impaired physical and mental health. Psychological conditions (notably depression and PTSD), substance use and abuse, domestic and gun-related violence, relationship instability, and hunger in low-income communities, especially among women of color, are discussed in detail. In terms of solutions, the book's contributors identify areas for major policy reform and make potent recommendations for community outreach, wide-scale intervention, and sustained advocacy. Among the topics covered: - The intersection of women's health and poverty. - Poverty, personal experiences of violence, and mental health. - The role of social support for women living in poverty. - The logic of exchange sex among women living in poverty. - Physical safety and neighborhood issues. - Exploring the complex intersections between housing environments and health behaviors among women living in poverty. A stark reminder that health should be considered a basic human right, Poverty in the United States: Women's Voices is a necessary reference for research professionals particularly interested in women's studies, HIV/AIDS prevention, poverty, and social policy.
Keywords: Social sciences.; Public health.; Social policy.; Social work.; elektronické knihy; electronic books